Філософська парадигма художнього перекладу: феномен нерозуміння "чужого" слова й тексту - Лімборський, І.В. (Слово і Час, 2019)
У статті проаналізовано філософські аспекти проблеми нерозуміння перекладачем тексту оригіналу, який завжди постає як культурний і ментальний досвід “чужої” системи художнього мислення. Перекладач тут виступає як посередник, котрий намагається “перенести” не лише художнє слово й текст у “свою” культуру, а й відтворює “чужу” дійсність в образах і символах “іншої” системи національного смислорозуміння. При цьому природно виникають моменти ментальних розбіжностей, семантичних “розривів” і трансформацій між текстами оригіналу й перекладу. А це породжує проблему з особливим метафізичним статусом, коли момент нерозуміння початкового тексту продиктований низкою чинників, зокрема й тих, що лежать за межами текстів оригіналу й перекладу. The paper analyzes philosophic aspects of the translator’s misunderstanding of the original text which always refl ects cultural and mental experience of the ‘other’ system of literary thinking. The translator is a mediator, who not only tries to insert a literary word and a text into ‘our’ culture, but also depicts ‘other’ reality in terms of symbols and images of the ‘other’ system of national understanding of senses. It is obvious that there are a lot of mental and semantic differences and transformations between the original text and the translation. This is a problem with a specific metaphysical status, when the misunderstanding of the original text may be caused by a number of aspects, some of which lie outside the text itself and its translation. The search for the new forms of thinking beyond the traditional stereotypes of rationality and self-evidence of “cogito” creates a new approach to the tasks and the essence of literary translation. Today one may confidently say that a new ethics, psychology and aesthetics of literary translation were born. The postmodern crisis of communication, as well as multicultural diversity and transcultural dialogue stimulated new forms and mechanisms for representing ‘other’ cultural experience (the experience of the ‘other’/‘alien’). According to the new paradigm of literary translation the translator must be focused on the philosophical aspects of the translation process. This is not only about the connection between the ‘subject’ and the ‘word’, or ‘thought’ and ‘experience’ that should have been reproduced in translation, but also about a specific metaphysical basis for the new process of thinking about a word and its role in overcoming the situation of misunderstanding of the ‘other’ literary text that presents other literary national tradition. The author of the paper comes to the conclusion that the phenomenon of misunderstanding of the ‘other’ word and text stems from the possibility of reading and rereading the text falsely. At the same time, the ‘misunderstanding’ of the original text gives an important chance to the translator for reading and rereading the original text alternatively.